KEMUDAHAN APLIKASI GOOGLE FORM SELAMA PROSES PEMBELAJARAN SISWA MASA PANDEMI COVID 19 - Conny Conny (Inteligensi : Jurnal Ilmu Pendidikan, 2021)
The purpose of this study was to obtain information about the used of the google form application during the pandemic at SMP Negeri 5 Tarakan. This study used a descriptive quantitative method with survey data collection techniques and documentation. Respondents in this study were 50 students randomly. The results of this study was students can take advantage of the google form application during learning during the Covid-19 pandemic, because of the ease of access which was approved by 92% of students, the ease of filling features which were approved by 86% of students, accurate presentation which was approved by 84% of students. , and its non-paper-based use which is approved by 70% of students so that this google form application can be used easily during the learning process.